Personality styles and behavioral repertoires in girls with high abilities - Gómez Pérez, María del Mar; García Martín, María Belén; Calero García, María Dolores (Anales de Psicología / Annals of Psychology, 2026)
Several explanations have been given for underrepresentation of women within gifted population, including differences in personality traits, competencies and/or motivations, beliefs and gender stereotypes expectations, and gender-differentiated behaviors; which highlights the importance of including these factors in observation, evaluation and screening protocols for children and adolescents. Therefore, this study aims to define if there are significant differences in gender-related personality styles and behavior patterns in highly talented adolescents. Participants were 159 adolescents between 11-16 years of age, divided into two groups. (1) High abilities group: a group of 85 adolescents (40 boys, 45 girls); (2) Typical group: a group of 74 adolescents (49 boys, 25 girls). All participants were assessed using personality, resilience, perfectionism, rule-following, perseverative thinking and experimental avoidance tests. Results revealed that gifted girls had higher scores than boys in some personality styles and behavior patterns considered as “negative”. Specifically, girls score significantly higher in anxiety, dominance, aggressiveness, among others and lower than boys on emotional stability, self-concept, self-confidence and cognitive control. Finally, implications for assessing and supporting gifted population are discussed.